Dynamic screen painter / Yee Chee Huan - Yee, Chee Huan (2004)
Dynamic Screen Painter (DSP) is a Web-based system. The development of this project actually is to provide a dynamic environment to the user where the user can use this system to change or modify web form inside a database. Web form is a form for the user to key in information into the database or as a "middle manï¿½ between the user and the database. So, through DSP, the users can retrieve the related forms from the database to use or to modify it to suit their demand base on the situation. For example, when there is a new project arise, the existing web form use for collecting a project information may be not suitable anymore. For these purpose, DSP provide a few feature for the users such as change the form layout to make it more arrange, add or delete the field exist on the form for certain purpose and etc. At the same time also, a set of code will be generated automatically base on the form layout and apply in the system once the form is generated so that the form can run immediately in the system. There are 2 main section in the DSP they are the generator part and administrator part. The project is developed by ASP.NET with C# and Microsoft SQL Server 2000 as the database. The methodology used to develop this system is the V model.